The Effects of Nurse Staffing and Nurse Education on Patient Deaths in Hospitals With Different Nurse Work Environments - Aiken, Linda H. (2011)
CONTEXT: Better hospital nurse staffing, more educated nurses, and improved nurse work environments have been shown to be associated with lower hospital mortality. Little is known about whether and under what conditions each type of investment works better to improve outcomes. OBJECTIVE: To determine the conditions under which the impact of hospital nurse staffing, nurse education, and work environment are associated with patient outcomes. DESIGN, SETTING, AND PARTICIPANTS: Outcomes of 665 hospitals in four large states were studied through linked data from hospital discharge abstracts for 1,262,120 general, orthopedic, and vascular surgery patients, a random sample of 39,038 hospital staff nurses, and American Hospital Association data. MAIN OUTCOME MEASURES: 30-day inpatient mortality and failure-to-rescue. RESULTS: The effect of decreasing workloads by one patient/nurse on deaths and failure-to-rescue is virtually nil in hospitals with poor work environments, but decreases the odds on both deaths and failures in hospitals with average environments by 4%, and in hospitals with the best environments by 9 and 10% respectively. The effect of 10% more BSN nurses decreases the odds on both outcomes in all hospitals, regardless of their work environment, by roughly 4%. CONCLUSIONS: While the positive effect of increasing percentages of BSN nurses is consistent across all hospitals, lowering the patient-to-nurse ratios markedly improves patient outcomes in hospitals with good work environments, slightly improves them in hospitals with average environments, and has no effect in hospitals with poor environments.